Optimasi Proses Pembuatan Asap Cair dari Tempurung Kelapa Melalui Response Surface Methodology (RSM) - Kholisoh, Siti Diyar; Achmad, Zubaidi; Hadi, Faizah (Jurnal Teknologi, 2023)
Response Surface Methodology (RSM) is a collection of mathematical and statistical techniques that are useful for analyzing complex processes that are influenced by several variables. This research aimed to apply RSM in optimizing the process of making liquid smoke from coconut shell pyrolysis. Optimum process conditions were reviewed based on the content of several functional compounds in liquid smoke including carbonyl content, phenol content, and acid content. The process variables comprised pyrolysis temperature (within the temperature range of 350 oC as low level (-1) and 450 oC as high level (+1)), pyrolysis time (within the range of 45 minutes as low level (-1) and 75 minutes as high level (+1)), and the water content in the coconut shell (within the range of 10% water content as low level (-1) and 20% as high level (+1)). This study results showed that the best carbonyl content in liquid smoke was 3.58% at temperature of 395 oC, pyrolysis time of 60 minutes, and water content of 16%. The optimum phenol content of 5.55% was achieved with a combination of pyrolysis time of 65 minutes and water content of 15.5%. Based on the acid content, an optimum value of 19.55% was obtained at a combination of pyrolysis time of 62 minutes and water content of 15.5%. The hypothesis H0 could be accepted statistically for the carbonyl content.